Investigation on natural gas hydrate dissociation from a slurry to a water-in-oil emulsion in a high-pressure flow loop - Shi, Bo-Hui; Song, Shang-Fei; Lv, Xiao-Fang; Li, Wen-Qing; Wang, Ying; Ding, Lin; Liu, Yang; Yang, Ju-Heng; Wu, Hai-Hao; Wang, Wei; Gong, Jing (Fuel (Guildford), 2018)
Investigations of natural gas hydrate dissociation from a slurry to a water-in-oil emulsion are conducted in a high-pressure hydrate experimental flow loop equipped with on-line microcosmic instruments including a focused beam reflectance measurement (FBRM) probe and a particle video microscope (PVM) probe. Three stages of the dissociation processes are observed and sketched in a conceptual mechanistic diagram, including initial dissociation with agglomeration, dissociation with breakage and re-aggregation, and thorough dissociation. The influences of initial pressure, flow rate, and water cut on hydrate dissociation are discussed. The pressure drop is increased by hydrate particle agglomeration, which increases the risk of hydrate plugging; thus, hydrate systems require close monitoring during the hydrate slurry dissociation process. Based on the classical kinetics theory, an improved hydrate dissociation model is developed by introducing a coupled heat- and mass-transfer influence coefficient and by considering the changes in the hydrate dissociated area based on the chord length data recorded by the FBRM probe. The intrinsic rate constant for natural gas hydrate dissociation is within the range of 1.41 × 103–7.18 × 104mol·Pa−1·s−1·m−2, and the activation energy of dissociation ranges from 68.2 to 72.3 kJ·mol−1. The reported investigation is significant for the application of hydrate slurries in risk-management methods to address issues of hydrate flow assurance in deep-water systems.